Research on the Confucian revival in Slovenia - Rošker, Jana S. (Asian studies, 2024)
There has been a significant amount of research carried out in Slovenia on the revival of Confucianism, particularly since 2012 and 2014, when the first two research projects on this topic were approved. Members of the Department of Asian Studies at the Faculty of Arts, University of Ljubljana, have been consistently conducting research in Slovenia and various Chinese, Taiwanese, and East Asian archives and libraries. These efforts have led to several important publications in Slovene, English, and even Chinese, and represent an ongoing commitment that continues in the present day. Therefore, it is not surprising that the present special issue of the Slovenian academic journal Asian Studies, focusing on the Confucian revival, already marks the fourth special issue in this area of research.This review article’s objective is thus to summarize the key achievements of Slovenian research in this field and provide a comprehensive overview of the diverse Slovene re-search activities and publications related to Modern New Confucianism. It covers not only research on the revival of Confucianism in China and the broader Sinic region, but also includes Confucian studies in other East Asian regions and the wider Sinic area.
Keywords: Chinese philosophy in Slovenia; Chinese studies in Slovenia; Confucian revival; East Asian Confucianism; kitajska filozofija v Sloveniji; kitajske študije v Sloveniji; konfucijanski preporod; Modern Chinese philosophy; Modern New Confucianism; moderna kitajska filozofija; moderno novo konfucijanstvo; Sinology in Slovenia; slovenska sinologija; vzhodnoazijsko konfucijanstvo